Developing students’ learning autonomy through project work at a secondary school in Hanoi = Phát triển tính tự chủ trong học tập của học sinh thông qualàm việc dự án ở một trường cấp hai tại Hà Nội - Nguyễn, Hồng Nhung (2020)
The present study was conducted toaddress two issues:investigatingthe influence of project work on students‟ learning autonomy and exploringstudents‟ evaluationsofthe using project work indevelopingtheir learning autonomy. The instruments employed for data collection and analysis of the study included two questionnaires, an interview with ten students, students‟ diaries, and observation. The findings showed that project work was beneficial to help studentstoimprove their learning autonomy. It also revealed that students highly recommendeddoingprojectsto enhance learning autonomythough they faced up with some difficulties in doing the projects. Based on the findings, some implications would be suggested for both the teacher and the students. With all this information, this study is expected to be significant to both teachers and students in teaching and learning process